Intact recognition, but attenuated adaptation, for biological motion in youth with autism spectrum disorder. Issue 10 (25th January 2016) - van Boxtel, Jeroen J. A.; Dapretto, Mirella; Lu, Hongjing
Abstract : Given the ecological importance of biological motion and its relevance to social cognition, considerable effort has been devoted over the past decade to studying biological motion perception in autism. However, previous studies have asked observers to detect or recognize briefly presented human actions placed in isolation, without spatial or temporal context. Research on typical populations has shown the influence of temporal context in biological motion perception: prolonged exposure to one action gives rise to an aftereffect that biases perception of a subsequently displayed action. Whether people with autism spectrum disorders (ASD) show such adaptation effects for biological motion stimuli remains unknown. To address this question, this study examined how well youth with ASD recognize ambiguous actions and adapt to recently‐observed actions. Compared to typically‐developing (TD) controls, youth with ASD showed no differences in perceptual boundaries between actions categories, indicating intact ability in recognizing actions. However, children with ASD showed weakened adaptation to biological motion. It is unlikely that the reduced action adaptability in autism was due to delayed developmental trajectory, as older children with ASD showed weaker adaptation to actions than younger children with ASD. Our results further suggest that high‐level (i.e., action) processing weakens with age for children with ASD, but this change may be accompanied by a potentially compensatory mechanism based on more involvement of low‐level (i.e., motion) processing. Autism Res 2016, 9: 1103–1113 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.